The Impact of Collaborative Problem-Solving Learning on Scientific Reasoning and the Halal Lifestyle Awareness of Class VIII Students at MTsN 2 Subang in Studying the Human Digestive System - Umusalamah, N.Dede; Farida , Ida; Windayani, Neneng; Nurdin , Dian K.; Wiwaha, Syahid Mujahid (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
Problems related to low scientific reasoning abilities and the application of halal lifestyle values among class VIII students on the subject of the human digestive system prompted the implementation of this research. The research aims to measure the effect of Collaborative Problem Solving (CPS)-based teaching on improving scientific reasoning and practicing halal lifestyles. The intervention was implemented through a pre-experimental one-group pretest-posttest design involving 30 MTsN 2 Subang students, with data collected through essay tests before and after the intervention and analyzed using the paired sample t-test. The results of the analysis show a significant increase in scientific reasoning scores and implementation of a halal lifestyle (significance value < 0.05), confirming the effectiveness of CPS in facilitating in-depth understanding of the human digestive system material. The discussion reveals that the CPS method triggers students' active involvement in collaborative problem solving, contributing to improving critical thinking skills and integrating halal values. These findings provide important implications for the development of innovative learning strategies as well as the integration of scientific values and halal ethics in the educational curriculum. [Permasalahan terkait rendahnya kemampuan penalaran ilmiah dan penerapan nilai gaya hidup halal di kalangan siswa kelas VIII pada materi sistem pencernaan manusia mendorong dilaksanakannya penelitian ini. Penelitian bertujuan mengukur pengaruh pengajaran berbasis Collaborative Problem Solving (CPS) terhadap peningkatan nalar ilmiah dan pengamalan pola hidup halal. Intervensi diterapkan melalui desain pra-eksperimental one-group pretest-posttest yang melibatkan 30 siswa MTsN 2 Subang, dengan data dikumpulkan melalui tes esai sebelum dan sesudah intervensi serta dianalisis menggunakan uji paired sample t-test. Hasil analisis menunjukkan peningkatan signifikan skor penalaran ilmiah dan penerapan gaya hidup halal (nilai signifikansi < 0,05), menegaskan efektivitas CPS dalam memfasilitasi pemahaman mendalam terhadap materi sistem pencernaan manusia. Pembahasan mengungkapkan bahwa metode CPS memicu keterlibatan aktif siswa dalam pemecahan masalah secara kolaboratif, berkontribusi pada peningkatan keterampilan berpikir kritis dan pengintegrasian nilai-nilai halal. Temuan ini memberikan implikasi penting bagi pengembangan strategi pembelajaran inovatif serta integrasi nilai keilmuan dan etika halal dalam kurikulum Pendidikan].